2015
DOI: 10.1098/rspb.2015.0440
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and scale-dependent evolutionary trends in the body size of crustaceans

Abstract: The ecological and physiological significance of body size is well recognized. However, key macroevolutionary questions regarding the dependency of body size trends on the taxonomic scale of analysis and the role of environment in controlling long-term evolution of body size are largely unknown. Here, we evaluate these issues for decapod crustaceans, a group that diversified in the Mesozoic. A compilation of body size data for 792 brachyuran crab and lobster species reveals that their maximum, mean and median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
(84 reference statements)
1
17
0
Order By: Relevance
“…The diversity and body size of true crabs and lobsters first increased significantly as part of the Mesozoic decapod revolution (Klompmaker et al . , ), followed by a decrease in raw genus richness for lobsters (Schweitzer & Feldmann ) and an increase in raw brachyuran species richness (Schweitzer & Feldmann ).…”
Section: Discussionmentioning
confidence: 98%
“…The diversity and body size of true crabs and lobsters first increased significantly as part of the Mesozoic decapod revolution (Klompmaker et al . , ), followed by a decrease in raw genus richness for lobsters (Schweitzer & Feldmann ) and an increase in raw brachyuran species richness (Schweitzer & Feldmann ).…”
Section: Discussionmentioning
confidence: 98%
“…The most effective response to increasing protrusion in predators is likely to be for prey to reduce the chances of visual detection. Size reduction has been previously suggested as a predation-avoidance mechanism in copepods [21], and there is evidence that reef-associated crabs decreased in size in the Cretaceous [22]. Indeed, on modern coral reefs, the mean size of crustaceans is only 0.8 mm [23].…”
Section: The Ecological Implications Of Protrusionmentioning
confidence: 97%
“…In regard to the effect of intra-family exoskeleton surface area variation, each arthropod basibiont does not provide the same target area for bryozoan larval settlement. Klompmaker et al (2015) found that maximum, mean and median body size increased for crabs and lobsters over the course of the Mesozoic. They argued that this long-term increase in body size of crabs and lobsters, coupled with their increased diversity and abundance, suggests that their ecological impact may have increased over evolutionary time.…”
Section: Discussionmentioning
confidence: 94%
“…anthropogenic greenhouse gas emissions and global warming). Studies on arthropods (Minelli et al 2013;Klompmaker et al 2015) and bryozoans (McKinney & Jackson 1989;Taylor & Waeschenbach 2015) often use biodiversity time series data to infer evolutionary causality. When trying to interpret biodiversity time series data, it is important to keep in mind that temporal correlation does not necessarily imply causation (Hannisdal & Liow 2018).…”
mentioning
confidence: 99%